2016
DOI: 10.1108/ijppm-03-2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing labor productivity on construction sites

Abstract: Purpose – Productivity is a worldwide problem and efforts have been made over the last three decades or so to explore ways to increase the rate of productivity on construction sites. The purpose of this paper is to investigate the state of the art in productivity research and to present the findings of a survey into the factors that can impair productivity on site. Design/methodology/approach – A literature review is structured under fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 91 publications
(80 reference statements)
4
93
1
5
Order By: Relevance
“…In the existing literature, it was revealed that productivity has been growing at 1% every year and the efficiency of workers is about 40% in the construction sector (Prabhu & Ambika, 2013). The common causes of low producitivity include mismanagement of construction materials, design errors, communication problems and inexperience of project team members, among others (Dai et al, 2007;Naoum, 2016). Based on the causes of low productivity, it is evident that poor management of site activities and pre-construction phase are the main reasons for low productivity.…”
Section: Introductionmentioning
confidence: 99%
“…In the existing literature, it was revealed that productivity has been growing at 1% every year and the efficiency of workers is about 40% in the construction sector (Prabhu & Ambika, 2013). The common causes of low producitivity include mismanagement of construction materials, design errors, communication problems and inexperience of project team members, among others (Dai et al, 2007;Naoum, 2016). Based on the causes of low productivity, it is evident that poor management of site activities and pre-construction phase are the main reasons for low productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Construction industry in many developing countries are greatly concerned with low level of skilled workers' productivity due to economic, social, physical and psychological related factors influencing the performance of the skilled workers [47]. Low productivity of skilled workers' is one of the most serious task facing the construc-tion industry especially in developing countries such as Malaysia, Indonesia, Singapore, Hong Kong, and other states in South east Asia [40].…”
Section: Introductionmentioning
confidence: 99%
“…The other option is to use survey research to uncover and prioritise the most important factors amongst those sourced via existing knowledge. See, for example, Naoum's [7] work, which considers 46 factors grouped into five categories (pre-construction, during construction, management, organisational, motivational and social). Several papers contain lengthy lists of factors, for instance, Dai et al [8] identified 83 (at project level, grouped into the following categories: supervisor direction, communication, safety, tools and consumables, materials, engineering drawing management, labour, foreman, superintendent, project management, construction equipment), while Tsehayae and Robinson Fayek [9] instead collected 169 factors (grouped according to levels: activity, project, organisational, provincial, national, global).…”
Section: Factors Influencing Productivitymentioning
confidence: 99%